Immune Thrombocytopenia in a worker exposed to toluene: a case report - Eric Slawka; Margarida Lourenço Castelló; Gabriel Machado Romão da Silva; Angelica dos Santos Vianna (Asia Pacific Journal of Medical Toxicology)
Introduction: Immune thrombocytopenia (ITP) is the most common cause of isolated thrombocytopenia in healthy individuals and can be classified as either primary or secondary. Drug use is an identifiable underlying cause for ITP. Toluene is a widely used solvent that is often contaminated with small amounts of benzene, a hematotoxic agent that can cause thrombocytopenia. Herein, we report a case of ITP in a patient with long-term low-level exposure to toluene in the workplace.Case Report: A 34-year-old white female chemistry technician presented to a teaching hospital in Rio de Janeiro, Brazil, in 2002, with a 2-year history of isolated thrombocytopenia, and low-level occupational exposure to toluene for more than a decade. She had bruises on the physical exam, and platelets count of 40.000 µL. A diagnosis of primary ITP aggravated by benzene-contaminated toluene exposure was made. The treatment included definitive removal from exposure and changes in activities, with gradual improvement in the clinical condition and platelet count, although without normalization.Discussion: We addressed the role of benzene as a toluene contaminant and an aggravating agent of primary ITP, a multifactorial disease that arises from different mechanisms. Although several substances may cause ITP, little attention has been paid to the role of toxicants such as benzene, a well-known hematotoxic agent.Conclusion: This case highlights the role of benzene-contaminated toluene in ITP. As benzene is a hematotoxic agent, we recommend that proper health and environmental evaluations should consider benzene exposure in workplaces where toluene is used.